Can ammonia tolerance amongst lichen functional groups be explained by physiological responses? - Munzi, S; Cruz, C; Branquinho, C; Pinho, P; Leith, I D; Sheppard, L J (Environmental pollution (Barking, Essex : 1987), 2014)
Ammonia (NH3) empirical critical levels for Europe were re-evaluated in 2009, based mainly on the ecological responses of lichen communities without acknowledging the physiological differences between oligotrophic and nitrophytic species. Here, we compare a nitrogen sensitive lichen (Evernia prunastri) with a nitrogen tolerant one (Xanthoria parietina), focussing on their physiological response (Fv/Fm) to short-term NH3 exposure and their frequency of occurrence along an NH3 field gradient. Both frequency and Fv/Fm of E. prunastri decreased abruptly above 3 μg m(-3) NH3 suggesting direct adverse effects of NH3 on its photosynthetic performance. By contrast, X. parietina increased its frequency with NH3, despite showing decreased capacity of photosystem II above 50 μg m(-3) NH3, suggesting that the ecological success of X. parietina at ammonia-rich sites might be related to indirect effects of increased nitrogen (NH3) availability. These results highlight the need to establish NH3 critical levels based on oligotrophic lichen species.
Keywords: Critical levels; Environmental protection policy; Evernia prunastri; nitrogen; Xanthoria parietina

Current ozone levels threaten gross primary production and yield of Mediterranean annual pastures and nitrogen modulates the response - Calvete-Sogo, Héctor; Elvira, Susana; Sanz, Javier; González-Fernández, Ignacio; García-Gómez, Héctor; Sánchez-Martín, Laura; Alonso, Rocío; Bermejo-Bermejo, Victoria (Atmospheric Environment, 2014)
Pastures are among the most important ecosystems in Europe considering their biodiversity and distribution area. However, their response to increasing tropospheric ozone (O3) and nitrogen (N) deposition, two of the main drivers of global change, is still uncertain. A new Open-Top Chamber (OTC) experiment was performed in central Spain, aiming to study annual pasture response to O3 and N in close to natural growing conditions. A mixture of six species of three representative families was sowed in the field. Plants were exposed for 40 days to four O3 treatments: filtered air, non-filtered air (NFA) reproducing ambient levels and NFA supplemented with 20 and 40 nl l-1 O3. Three N treatments were considered to reach the N integrated doses of “background”, +20 or +40 Kg N ha-1. Ozone significantly reduced green and total aboveground biomass (maximum reduction 25%) and increased the senescent biomass (maximum increase 40%). Accordingly, O3 decreased community Gross Primary Production due to both a global reduction of ecosystem CO2 exchange and an increase of ecosystem respiration. Nitrogen could partially counterbalance O3 effects on aboveground biomass when the levels of O3 were moderate, but at the same time O3 exposure reduced the fertilization effect of higher N availability. Therefore, O3 must be considered as a stress factor for annual pastures in the Mediterranean areas.
Keywords: annual grasslands interactions; Critical levels; Dehesa; Global change; nitrogen; tropospheric ozone

Fertilization regime interacts with fall temperature in the nursery to determine the frost and drought tolerance of the Mediterranean oak Quercus ilex subsp. ballota - Heredia-Guerrero, Norberto; Oliet, Juan a; Villar-Salvador, Pedro; Benito, Luis F; Peñuelas, Juan L (Forest Ecology and Management, 2014)
Nitrogen fertilization in the nursery usually improves the transplanting performance of Mediterranean oaks. However, high N fertilization can reduce seedling stress tolerance, probably depending on the environmental conditions under which plants grow. We hypothesize that high N fertilization under mild fall conditions reduces cold and drought acclimation. To assess this hypothesis, we studied if fall temperature differences among cultivation locations influence the effect of N fertilization regime on cold and drought tolerance, N status and growth in the evergreen Mediterranean oak Quercus ilex subsp. ballota (Desf.) Samp. Plants were cultivated in two nurseries of distinct fall temperature conditions (mild and cold fall nurseries) under four fertilization regimes: Low and high N at constant rate (total N, 33 and 175mgseedling−1), high N at exponential rate (175mgNseedling−1) and fall N loading (89mgNseedling−1). Seedling water relations, survival to a −12°C frost and leaf soluble carbohydrates concentration were assessed three times in the fall, and shoot elongation was measured weekly through the fall. Moreover, seedling mass and N concentration were measured at the end of the fall. Fall loaded seedlings had the highest tissue N concentration, while seedling mass was highest in the high N constant and exponential fertilization regimes. Seedlings at the cold fall nursery concentrated more N but were smaller than seedlings at the mild fall nursery. Cessation of shoot elongation in the mild fall nursery occurred 1month later than in the cold location and high N exponentially-fertilized plants ceased shoot elongation later than the rest of fertilization treatments. Seedlings at the mild fall location had lower drought and cold tolerance than plants at the cold fall site. At mid fall, exponential fertilization at the mild nursery reduced seedling frost and drought tolerance, but treatment differences vanished at the end of the fall. In contrast, fertilization regime did not affect either cold or drought tolerance of seedlings at the cold fall nursery. Across dates and nurseries, frost survival was positively related to leaf soluble carbohydrates concentration and dry weight fraction. Beside, degree of cold acclimation decreased with shoot elongation cessation date and increased with leaf soluble carbohydrates concentration, suggesting a link between shoot growth activity, soluble carbohydrates, and frost tolerance. We conclude that Q. ilex subsp. ballota hardening is reduced by high N exponential fertilization mainly under mild fall conditions, while fall loading and constant low N fertilization did not affect hardening.
Keywords: Cold acclimation; Hardening; nitrogen; Nutrient loading; Osmotic potential; Soluble carbohydrate

Is there a species spectrum within the world-wide leaf economics spectrum? Major variations in leaf functional traits in the Mediterranean sclerophyll Quercus ilex - Niinemets, Ülo (New Phytologist, 2014)
The leaf economics spectrum is a general concept describing coordinated variation in foliage structural, chemical and physiological traits across resource gradients. Yet, within this concept, the role of within-species variation, including ecotypic and plastic variation components, has been largely neglected. This study hypothesized that there is a within-species economics spectrum within the general spectrum in the evergreen sclerophyll Quercus ilex which dominates low resource ecosystems over an exceptionally wide range. An extensive database of foliage traits covering the full species range was constructed, and improved filtering algorithms were developed. Standardized data filtering was deemed absolutely essential as additional variation sources can result in trait variation of 10–300%, blurring the broad relationships. Strong trait variation, c. two-fold for most traits to up to almost an order of magnitude, was uncovered. Although the Q. ilex spectrum is part of the general spectrum, within-species trait and climatic relationships in this species partly differed from the overall spectrum. Contrary to world-wide trends, Q. ilex does not necessarily have a low nitrogen content per mass and can increase photosynthetic capacity with increasing foliage robustness. This study argues that the within-species economics spectrum needs to be considered in regional- to biome-level analyses.
Keywords: bioclimatic niche; climatic drivers; dry mass per unit area; leaf economics spectrum; leaf physiognomy; nitrogen; photosynthesis; trait relationships

Tools for determining critical levels of atmospheric ammonia under the influence of multiple disturbances - Pinho, P; Llop, E; Ribeiro, M C; Cruz, C; Soares, A; Pereira, M J; Branquinho, C (Environmental Pollution, 2014)
Critical levels (CLEs) of atmospheric ammonia based on biodiversity changes have been mostly calculated using small-scale single-source approaches, to avoid interference by other factors, which also influence biodiversity. Thus, it is questionable whether these CLEs are valid at larger spatial scales, in a multi- disturbances context. To test so, we sampled lichen diversity and ammonia at 80 sites across a region with a complex land-cover including industrial and urban areas. At a regional scale, confounding factors such as industrial pollutants prevailed, masking the CLEs. We propose and use a new tool to calculate CLEs by stratifying ammonia concentrations into classes, and focusing on the highest diversity values. Based on the significant correlations between ammonia and biodiversity, we found the CLE of ammonia for Mediterranean evergreen woodlands to be 0.69 mgm?3, below the previously accepted value of 1.9 mgm?3, and below the currently accepted pan-European CLE of 1.0 mgm?3
Keywords: Air Pollutants; Air Pollutants: analysis; ammonia; Ammonia: analysis; Atmosphere; Atmosphere: chemistry; Biodiversity; Critical thresholds; Environmental Monitoring; Environmental Monitoring: methods; Eutrophication; Functional groups; Global change; lichens; Lichens: chemistry; Lichens: classification; nitrogen

Field-simulated droughts affect elemental leaf stoichiometry in Mediterranean forests and shrublands - Sardans, Jordi; Rivas-Ubach, Albert; Estiarte, Marc; Ogaya, Romà; Penuelas, Josep (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2013)
This study evaluated the change induced by the year season and by experimentally induced drought on foliar element stoichiometry of the predominant woody species (Quercus ilex and Erica multiflora) in two Mediterranean ecosystems, a forest and a shrubland. This study is based in two long-term (11 yr) field experiments that simulated drought throughout the annual cycle. The effects of experimental droughts were significant but weaker than the changes produced by ontogeny and seasonality. Leaf N and P concentrations were higher in spring (the main growing season) in E. multiflora and, in Q. ilex in autumn (a period of additional growth). Leaf N:P ratios were lower in spring. In Q. ilex, the highest leaf K concentrations and leaf K:P ratios, and the lowest leaf C:K and N:K ratios, occurred in summer, the season when water stress was greatest. In E. multiflora, leaf K concentrations and K:P ratios were highest, and leaf C:K and N:K ratios were lowest in the plants from the drought-treated plots. The plant capacity to change K concentrations in response to seasonality and to drought is at least as great as the capacity to change N and P concentrations. The results underscore the importance of K and its stoichiometry relative to C, N and P in dry environments. These results indicate first, that N:P ratio shifts are not uniquely related to growth rate in Mediterranean plants but also to drought, and second, that there is a need to take into account K in ecological stoichiometry studies of terrestrial plants. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: climate change; Drought; Growth rate hypothesis; N:P; nitrogen; Ontogeny; phosphorus; Potassium

Tree species is the major factor explaining C:N ratios in European forest soils - Cools, N.; Vesterdal, L.; De Vos, B.; Vanguelova, E.; Hansen, K.; Vos, B. De (Forest Ecology and Management, 2013)
The C:N ratio is considered as an indicator of nitrate leaching in response to high atmospheric nitrogen (N) deposition. However, the C:N ratio is influenced by a multitude of other site-related factors. This study aimed to unravel the factors determining C:N ratios of forest floor, mineral soil and peat top soils in more than 4000 plots of the ICP Forests large-scale monitoring network. The first objective was to quantify forest floor, mineral and peat soil C:N ratios across European forests. Secondly we determined the main factors explaining this C:N ratio using a boosted regression tree analysis (BRT), including fifteen site and environmental variables. Ninety-five percent of the C:N ratios were between 16 and 44 in the forest floor, between 13 and 44 in the peat topsoil and between 10 and 32 in the mineral topsoil. Within the aerated forest floor and the mineral soil, the C:N ratios decreased with depth, while in the hydromorphic forest floor and the peats no clear trend with depth was observed. Tree species was clearly the most important explanatory variable for the C:N ratio in both forest floors and topsoils, while it was soil type in the deeper mineral soil layers. The lowest C:N ratios both in the forest floor and the top mineral soil were found in black locust (Robinia pseudoacacia L.) and black alder (Alnus glutinosa L.) stands, both N fixing tree species. While in the forest floor the highest C:N ratios were found in evergreen species like pine, cork oak (Quercus suber L.) and eucalyptus, the pine species and Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) showed the highest C:N ratios in the mineral soil. The second most important explanatory variable in the forest floor and mineral topsoil was the biogeographical zoning (ecoregion). In the peat topsoil and in the deeper mineral soil layers it was the humus type. Deposition and climatic variables were of minor importance at the European scale. Further analysis for eight main forest tree species individually, showed that the influence of environmental variables on C:N ratios was tree species dependent. For Aleppo pine (Pinus halepensis Miller) and holm oak (Quercus ilex L.), both with a typical Mediterranean distribution, the relationship between N and S deposition and C:N ratio appeared to be positive. This study suggests that applying C:N ratios as a general indicator of the N status in forests at the European level, without explicitly accounting for tree species, is too simplistic and may result in misleading conclusions.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Carbon; Forest floor; ICP forests; Mineral soil; nitrogen; Tree species

Changes in atmospheric deposition and streamwater chemistry over 25 years in undisturbed catchments in a Mediterranean mountain environment. - Avila, Anna; Rodà, Ferran (The Science of the total environment, 2012)
Surface water chemistry has changed in response to reduced atmospheric deposition of sulphur and acidity in many regions of Europe and North America. Most of these studies come from acidic or low-alkalinity surface waters under high acidic deposition. Mediterranean climates offer a different biogeochemical context, characterised by streamwaters of higher alkalinity and low acid inputs. In this paper, we use surveys of streamwater chemistry conducted in 1981-1984 and again in 2007 in the Montseny natural park (NE Spain) to test whether streamwaters of these well-buffered catchments respond to changes in atmospheric deposition, which has declined for S during the last decades in NE Spain while remaining about stable for nitrogen. The 23 sampled streams drained heathland, beech forests and evergreen oak forests in relatively undisturbed small catchments underlain by silicate bedrock. Bulk deposition of sulphate at Montseny decreased by 54% while nitrate bulk deposition increased (non-significantly) by 30% in this period. Total N deposition is estimated in the range 15-30 kg N ha(-1) y(-1) for NE Spain. This is well above threshold values (e.g. 10 kg N ha(-1) y(-1)) reported as starting nitrogen saturation symptoms in forest ecosystems in Europe. Baseflow sulphate concentrations decreased on average by 47 μeq L(-1) or 29% of early 1980s concentrations. Baseflow mean nitrate concentrations increased significantly but only from 5.5 to 8.9 μeq L(-1). Thus, despite decades of high N deposition, these ecosystems appear to be still far from N saturation. Baseflow alkalinity and base cation concentrations increased substantially, probably a combined result of decreased S deposition, enhanced silicate weathering under current higher temperatures, reduced plant cation uptake as vegetation matures, and slightly drier conditions in the survey of 2007. Overall, these well-buffered catchments have shown sizable changes in baseflow chemistry in response to changed atmospheric deposition and other environmental changes.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 22200374
Keywords: Alkalinity; Base cations; nitrogen; Quercus ilex; Streamwater chemistry; Sulphate

Acorn production is linked to secondary growth but not to declining carbohydrate concentrations in current-year shoots of two oak species - Alla, Arben Q.; Camarero, J. Julio; Maestro-Martínez, Melchor; Montserrat-Martí, Gabriel (Trees, 2011)
In trees, reproduction constitutes an important resource investment which may compete with growth for resources. However, detailed analyses on how growth and fruit production interact at the shoot level are scarce. Primary canopy growth depends on the development of current-year shoots and their secondary growth might also inﬂuence the number and size of fruits supported by them. We hypothesise that an enhanced thickening of currentyear shoots is linked positively to acorn production in oaks. We analysed the effect of acorn production on shoot growth of two co-occurring Mediterranean oak species with contrasting leaf habit (Quercus ilex, Quercus faginea). Length and cross-sectional area of current-year shoots, apical bud mass, number of leaves and acorns, xylem and conductive area, number of vessels of acorn-bearing and non-bearing shoots were measured in summer and autumn. Nitrogen and carbohydrates analyses were also performed in stems and leaves of both shoot types. Stem cross-sectional area increased in acorn-bearing shoots when compared with non-bearing shoots for both species and such surplus secondary growth was observed since summer. In bearing shoots, the total transversal area occupied by vessels decreased signiﬁcantly from basal to apical positions along the stem as did the xylem area and the number of vessels. Leaves of bearing shoots showed lower nitrogen concentration than those of non-bearing shoots. Carbohydrate concentrations did not differ in stems and leaves as a function of the presence of acorns. Such results suggest that carbohydrates may preferentially be allocated towards reproductive shoots, possibly through enhanced secondary growth, satisfying all their carbon demands for growth and reproduction. Our ﬁndings indicate that acorn production in the two studied oaks depends on shoot secondary growth.
Keywords: acorns; Mediterranean climate; nitrogen; non-structural carbohydrates; Quercus faginea; quercus ilex subsp. ballota; Stem diameter; Xylem

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Can NPK fertilizers enhance seedling growth and mycorrhizal status of Tuber melanosporum-inoculated Quercus ilex seedlings? - Suz, Laura M; Martín, María P; Fischer, Christine R; Bonet, José a; Colinas, Carlos (Mycorrhiza, 2010)
Although successful cultivation of the black truffle (Tuber melanosporum) has inspired the establishment of widespread truffle orchards in agricultural lands throughout the world, there are many unknowns involved in proper management of orchards during the 6-10 years prior to truffle production, and there are conflicting results reported for fertilizer treatments. Here, we systematically evaluate the combined effects of nitrogen, phosphorous, and potassium with different doses of each element, applied to either foliage or roots, on plant growth parameters and the mycorrhizal status of outplanted 3-year-old seedlings in five experimental Quercus ilex-T. melanosporum orchards. Fertilization did not significantly improve seedling aboveground growth, but the plants treated with the fertilizer 12-7-7 applied to the roots (HNr) displayed longer field-developed roots. Only the fertilizer with the highest dose of K (10-6-28) applied to the foliage (HKf) increased the probability of fine root tip colonization by T. melanosporum in field-developed roots. However, the plants treated with the same fertilizer applied to the soil (HKr) presented the highest probability for colonization by other competing mycorrhizal soil fungi. Potassium seems to have an important role in mycorrhizal development in these soils. Apart from T. melanosporum, we found 14 ectomycorrhizal morphotypes, from which seven were identified to species level, three to genus, two to family, and two remained unidentified by their morphological characteristics and DNA analyses.
Keywords: Black truffle; DNAanalysis; ectomycorrhiza; morphotyping; nitrogen; Phosphorous; Potassium; Truffle orchard

Microbial C, N and P in soils of Mediterranean oak forests: influence of season, canopy cover and soil depth - Aponte, Cristina; Marañón, Teodoro; García, Luis V. (Biogeochemistry, 2010)
In Mediterranean ecosystems the effect of aboveground and belowground environmental factors on soil microbial biomass and nutrient immobilization-release cycles may be conditioned by the distinctive seasonal pattern of the Mediterraneantype climates. We studied the effects of season, canopy cover and soil depth on microbial C, N and P in soils of two Mediterranean forests using the fumigation-extraction procedure. Average microbial values recorded were 820 lg C g -1 , 115 lg N g -1 and 19 lg P g -1 , which accounted for 2.7, 4.7 and 8.8% of the total pools in the surface soil, respectively. Microbial N and P pools were about 10 times higher than the inorganic N and P fractions available for plants. Microbial C values differed between forest sites but in each site they were similar across seasons. Both microbial and inorganic N and P showed maximum values in spring and minimum values in summer, which were positively correlated with soil moisture. Signiﬁcant differences in soil microbial properties among canopy cover types were observed in the surface soil but only under favourable environmental conditions (spring) and not during summer. Soil depth affected microbial contents which decreased twofold from surface to subsurface soil. Microbial nutrient ratios (C/N, C/P and N/P) varied with seasons and soil depth. Soil moisture regime, which was intimately related to seasonality, emerged as a potential key factor for microbial biomass growth in the studied forests. Our research shows that under a Mediterranean-type climate the interaction among season, vegetation type and structure and soil properties affect microbial nutrient immobilization and thus could inﬂuence the biogeochemical cycles of C, N and P in Mediterranean forest ecosystems.
Keywords: á; dynamics á; Microbial biomass; microbial biomass á nitrogen; nitrogen; Nutrient immobilization; nutrient immobilization á phosphorus; phosphorus; Plant; Plant–soil interactions; seasonal dynamics; soil interactions á seasonal; vegetation cover

Remobilization of acorn nitrogen for seedling growth in holm oak (Quercus ilex), cultivated with contrasting nutrient availability. - Villar-Salvador, Pedro; Heredia, Norberto; Millard, Peter (Tree physiology, 2010)
The relative contribution of nitrogen (N) reserves from seeds or uptake by the roots to the growth and N content of young seedlings has received little attention. In this study, we investigated the contribution of N from the acorn or uptake by the roots to the N content of holm oak (Quercus ilex L.) seedlings and determined if remobilization of acorn N was affected by nutrient availability in the growing media. Q. ilex seedlings were cultivated for 3 months, until the end of the second shoot flush of growth, with three N fertilization rates: 8.6 mM N, 1.4 mM N or no fertilization. Fertilizer N was enriched in (15)N. Between 62 and 75% of the N contained in high and low fertilized seedlings, respectively, at the end of the second flush of growth was derived from the acorn. However, the dependence on acorn N was greater during the early root growth and first shoot flush of growth and decreased during the second shoot flush of growth, with root uptake contributing 32-54% of plant new N in this latter developmental stage in high and low fertilized plants, respectively. Fertilization rate did not affect the amount of N taken up during the earliest developmental stages, but it increased it during the second shoot flush of growth. Fertilization increased the mass of the shoot segment formed during the second shoot flush of growth and reduced the root mass, with no effect on whole plant growth. Remobilization of acorn N was faster in unfertilized plants than in fertilized plants. It is concluded that the holm oak seedlings depend greatly upon acorn N until the end of the second shoot flush of growth, that significant root N uptake starts at the beginning of the second shoot flush of growth and that acorn N remobilization is a plastic process that is accelerated under extremely low substratum nutrient content.
Keywords: germination; nitrogen; Nitrogen Isotopes; Nitrogen Isotopes: metabolism; Nitrogen: metabolism; Quercus; Quercus: growth & development; Quercus: metabolism; Seedling; Seedling: growth & development; Seedling: metabolism; Seeds; Seeds: metabolism; Soil

Ex Vitro Acclimatization of Laelia halbingeriana Plants Grown in Different Media and Fertilization Doses - Heredia-Rendon, A; Enriquez-del Valle, J; Campos, G V; Marini, F; Velasco, V A; Damon, A (INTERNATIONAL SYMPOSIUM ON SOILLESS CULTURE AND HYDROPONICS, 2009)
In vitro plants of the orchid Laelia halbingeriana were obtained from seed germination. The plants were grown and established in different organic substrates mixes. The substrates resulted from the mix of compost and charcoal, land of mount and Holm oak bark, and peat and volcanic tuff. The plants were fertilized with four levels of nitrogen (0, 10, 30 and 50 mg L-1). Six months after the establishment, 64.84% to 80.22% of the plants were adapted to the climate conditions. The highest survival rates in plantlets were obtained in the adaptation conditions using peat-volcanic tuff and nitrogen doses of 30 and 50 mg L-1. These plants had an average of 8.01 cm height, 5.15 leafs, 2.66 pseudo-bulbs, 77 to 89 mg of total accumulated dry matter, and 42 to 45% of C in leaves and pseudo-bulbs. The fertilization had a significant effect (P <= 0.05) on the plants growth and a highly significant effect (P <= 0.01) on number of leaves, width of the major leaf and the number of pseudo-bulbs; The interaction substrates and fertilization had a highly significant effect (P <= 0.01) on the nitrogen content in leaves and pseudo-bulbs.
Keywords: development; in vitro; nitrogen; Orchidacea; Seeds

Materia orgánica de suelos bajo encinas. Mineralización de carbono y nitrógeno - Gonzalez Parra, J; Candás Villar, M A (Forest Systems, 2008)
Soil characteristics under evergreen oaks forest (Quercus rotundifolia Lam.) located at the East of Segovia were studied. The soils were formed from gneis and limestone. The whole soil was 0-20 cm depth. The soils were classified as mollic Leptosols, eutric Cambisols and calcaric Cambisols. Horizons sequences were the following: O, Ah1, Ah2, C and O, Ah1, Ah2, BC. Organic horizons (3-0 cm depth) were formed by the not-yet decomposed organic remains from evergreen oaks. Mean organic matter content was 25%. The C:N ratio was high and free organic carbon was near 90% of the total carbon, which correspond with a low degree of humification. Soil texture was loamy sand and sandy loam. Soils on limestone present the highest clay fraction contents. The bases saturation degree was high, being Ca 2+ the fundamental cation of exchange complex. Organic matter content and C:N ratio were lower in organic minerals horizons than in organic horizons. Humification degree was 60% with a predominance of HAs over FAs. The polimerization of humic substances makes possible the formation of humus «moder». Carbon mineralization to the total C was ten times higher than nitrogen mineralization in upper horizons. In all horizons the nitrification was higher than N mineralization. Carbon mineralization was lower and N mineralization was higher in deeper horizons compearing with upper horizons.
Keywords: mineralization; nitrogen; organic matter; Quercus rotundifolia; soils

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Parent material effects on Mediterranean woodland ecosystems in NE Spain - Kooijman, A M; Jongejans, J; Sevink, J (Catena, 2005)
A field survey of an evergreen Mediterranean woodland area in NE Spain on three silica-rich parent materials (granite, granodiorite and schist) was used to test whether parent material had a separate effect on ecosystem functioning in addition to aspect and position on the slope. As expected, vegetation was taller and denser on north-facing slopes and/or lower slope positions. However, parent material appeared to have additional effects, with significant increases in tree height, tree cover, shrub height and ratio of woodland to maquis vegetation from granite towards granodiorite and schist. There was also a parallel increase in mull humus forms, indicating increasing litter breakdown. The lower productivity on granite may be partly attributed to drought stress, as indicated by the greater proportion of shallow soils and the sandy to loamy sand texture. However, nutrient stress may be equally important. Plant N/P ratios were significantly greater on granite, and plant and soil P contents were less than on the other parent materials, suggesting that P-availability was limited on granite. The greater productivity of soils on schist than on granodiorite may reflect less severe drought stress because of their finer texture. These results suggest that parent material is an important factor regulating productivity in Mediterranean ecosystems through varying drought stress and availability of nutrients.
Keywords: biomass; Drought stress; nitrogen; Nutrient; phosphorus; Soil; Vegetation; water

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - Villar-Salvador, P.; Planelles, R.; Enrı́quez, E.; Rubira, J. Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - VILLAR-SALVADOR, P; Planelles, R; Enrı́quez, E; Rubira, J.Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species - Mediavilla, S.; Escudero, A. (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Leaf growth; leaf life span; mean residence time; nitrogen; phosphorus

Leaf life span differs from retention time of biomass and nutrients in the crowns of evergreen species - Mediavilla, S; Escudero, a (Functional Ecology, 2003)
* 1A long leaf life span has been interpreted as an adaptation to low nutrient availability. It is commonly assumed that a long leaf life span permits a longer utilization of nutrients in the leaf biomass and that this contributes to improving nutrient use efficiency. However, a long leaf life span is also associated with other leaf traits that reduce instantaneous productivity, which might reduce the growth rate of the leaf biomass and shorten the functional life of the leaf. * 2We studied the relationships between leaf life span and the retention time of biomass and nutrient pools in several woody species with different leaf life spans. We measured the monthly variations in the total number of leaves per annual shoot, mass per leaf, and N and P contents per leaf. With these data, the leaf life span and the mean residence time (MRT) of leaf biomass and nutrient pools were estimated. * 3The increase in the total number of leaves was fast in all species studied at the start of the growth season. In contrast, in evergreen species mass per leaf and total N and P contents per leaf increased gradually after the first year of life of the leaves, and the maximum mass and nutrient contents per leaf were attained only towards the end of the lifetime of the leaves. * 4Owing to the delay in the development of mass and nutrient pools with respect to leaf number dynamics, in evergreen species leaf life span was longer than the MRT of leaf biomass and nutrient pools because part of the leaf biomass and nutrient pool remained in the crown for a shorter time than the mean duration of the individual leaves. * 5The differences between leaf life span and the MRT of the biomass and nutrients increased with leaf life span. The slow growth of evergreen leaves therefore contributes to reduce the adaptive value of a long leaf life span as a mechanism to increase the duration of the photosynthetic machinery.
Keywords: Leaf growth; leaf life span; mean residence time; nitrogen; phosphorus

Nitrogen deposition in Mediterranean forests. - Rodà, F; Avila, a; Rodrigo, a (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Nitrogen deposition in Mediterranean forests. - Roda, F.; Avila, a; Rodrigo, A. (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
The following values have no corresponding Zotero field: accession-num: 11939283
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Photosynthetic responses to water deficit in six Mediterranean sclerophyll species: possible factors explaining the declining distribution of Rhamnus ludovici-salvatoris, an endemic Balearic species. - Gulías, J; Flexas, J; Abadía, A; Madrano, H (Tree Physiology, 2002)
We sought to explain the declining distribution in the Balearic Islands of the endemic shrub Rhamnus ludovici-salvatoris R. Chodat, by comparing its photosynthetic response to drought with that of several widely distributed, competing Mediterranean species (R. alaternus L., Quercus ilex L., Pistacia lentiscus L., Q. humilis Mill. and P. terebinthus L.). [ABSTRACT FROM PUBLISHER]
Keywords: chlorophyll fluorescence; deciduous; Drought; evergreen; Gas exchange; leaf mass area; nitrogen; Pistacia; Quercus; Rhamnus; xanthophyll cycle

Inflación del capital natural de la dehesa: hipótesis sobre la naturaleza caótica de la seca de los Quercus DENTRO DEL PROCESO DE LA SENESCENCIA FOLIAR - CUEVAS, S; TORRES, E; VÁZQUEZ, F.Mª.; López Arias, M; HERNÁNDEZ, A (III Congreso Forestal Español Congreso, 2001)
“Dehesa” is a gap forest yielding as an ecological-economic system (money-borrowed), poor soils (money-lender) upheld during optimal stopping millenia. Have supported multiple antropogenic nutrition disturbances during chaotic and resource routine affecting oak root uptake. Shoot nutrient odyssey is represented by cobweb model as price (nitrogen) evolution working by-product quantity (biomass). This trial evaluates cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia Lam.) harvest basic sustainability (HBS) or nitrogen leaf redemption, southern Extremadura situated, evaluating ecological economic orientor for ecosystem. Defective HBS management hypothesis is expound in the absence of forest management, leading to sickly phenomenon on forest health as oak decline. Parallelly, HBS is proposed as an cork quality indirect index. Leaf senescence fork leads to physiological imbalance and, in some final cases, whole canopy defoliation (tie break). K.W.: Cobweb model, Oak decline, Renewal, Optimal stopping Dehesa, Nitrogen.
Keywords: Cobweb model; nitrogen; Oak decline; Optimal stopping Dehesa; Renewal

Inflación del capital natural de la dehesa: hipótesis sobre la naturaleza caótica de la seca de los Quercus DENTRO DEL PROCESO DE LA SENESCENCIA FOLIAR - CUEVAS, S.; Torres, E.; VÁZQUEZ, F. Mª; López Arias, M.; HERNÁNDEZ, A. (III Congreso Forestal Español Congreso, 2001)
“Dehesa” is a gap forest yielding as an ecological-economic system (money-borrowed), poor soils (money-lender) upheld during optimal stopping millenia. Have supported multiple antropogenic nutrition disturbances during chaotic and resource routine affecting oak root uptake. Shoot nutrient odyssey is represented by cobweb model as price (nitrogen) evolution working by-product quantity (biomass). This trial evaluates cork oak (Quercus suber L.) and holm oak (Quercus rotundifolia Lam.) harvest basic sustainability (HBS) or nitrogen leaf redemption, southern Extremadura situated, evaluating ecological economic orientor for ecosystem. Defective HBS management hypothesis is expound in the absence of forest management, leading to sickly phenomenon on forest health as oak decline. Parallelly, HBS is proposed as an cork quality indirect index. Leaf senescence fork leads to physiological imbalance and, in some final cases, whole canopy defoliation (tie break). K.W.: Cobweb model, Oak decline, Renewal, Optimal stopping Dehesa, Nitrogen.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: Cobweb model; nitrogen; Oak decline; Optimal stopping Dehesa; Renewal

Interactive effects of nitrogen and phosphorus on the acclimation potential of foliage photosynthetic properties of cork oak, Quercus suber, to elevated atmospheric CO2 concentrations - Niinemets, Ü; Tenhunen, J D; Canta, N R; Chaves, M M; Faria, T; Pereira, J S; Reynolds, J F (Global Change Biology, 1999)
Leaf gas-exchange and chemical composition were investigated in seedlings of Quercus suber L. grown for 21 months either at elevated (700 μmol mol–1) or normal (350 μmol mol–1) ambient atmospheric CO2 concentrations, [CO2], in a sandy nutrient-poor soil with either ‘high’ N (0.3 mol N m–3 in the irrigation solution) or with ‘low’ N (0.05 mol N m–3) and with a constant suboptimal concentration of the other macro- and micronutrients. Although elevated [CO2] yielded the greatest total plant biomass in ‘high’ nitrogen treatment, it resulted in lower leaf nutrient concentrations in all cases, independent of the nutrient addition regime, and in greater nonstructural carbohydrate concentrations. By contrast, nitrogen treatment did not affect foliar N concentrations, but resulted in lower phosphorus concentrations, suggesting that under lower N, P use-efficiency in foliar biomass production was lower. Phosphorus deficiency was evident in all treatments, as photosynthesis became CO2 insensitive at intercellular CO2 concentrations larger than ≈ 300 μmol mol–1, and net assimilation rates measured at an ambient [CO2] of 350 μmol mol–1 or at 700 μmol mol–1 were not significantly different. Moreover, there was a positive correlation of foliar P with maximum Rubisco (Ribulose-1,5-bisphosphate carboxylase/oxygenase) carboxylase activity (Vcmax), which potentially limits photosynthesis at low [CO2], and the capacities of photosynthetic electron transport (Jmax) and phosphate utilization (Pmax), which are potentially limiting at high [CO2]. None of these potential limits was correlated with foliar nitrogen concentration, indicating that photosynthetic N use-efficiency was directly dependent on foliar P availability. Though the tendencies were towards lower capacities of potential limitations of photosynthesis in high [CO2] grown specimens, the effects were statistically insignificant, because of (i) large within-treatment variability related to foliar P, and (ii) small decreases in P/N ratio with increasing [CO2], resulting in balanced changes in other foliar compounds potentially limiting carbon acquisition. The results of the current study indicate that under P-deficiency, the down-regulation of excess biochemical capacities proceeds in a similar manner in leaves grown under normal and elevated [CO2], and also that foliar P/N ratios for optimum photosynthesis are likely to increase with increasing growth CO2 concentrations. Symbols: A, net assimilation rate (μmol m–2 s–1); Amax, light-saturated A (μmol m–2 s–1); α, initial quantum yield at saturating [CO2] and for an incident Q (mol mol–1); [CO2], atmospheric CO2 concentration (μmol mol–1); Ci, intercellular CO2 concentration (μmol mol–1); Ca, CO2 concentration in the gas-exchange cuvette (μmol mol–1); FB, fraction of leaf N in ‘photoenergetics’; FL, fraction of leaf N in light harvesting; FR, fraction of leaf N in Rubisco; Γ*, CO2 compensation concentration in the absence of Rd (μmol mol–1); Jmax*, capacity for photosynthetic electron transport; Jmc, capacity for photosynthetic electron transport per unit cytochrome f (mol e–[mol cyt f]–1 s–1); Kc, Michaelis-Menten constant for carboxylation (μmol mol–1); Ko, Michaelis-Menten constant for oxygenation (mmol mol–1); MA, leaf dry mass per area (g m–2); O, intercellular oxygen concentration (mmol mol–1); [Pi], concentration of inorganic phosphate (mM); Pmax*, capacity for phosphate utilization; Q, photosynthetically active quantum flux density (μmol m–2 s–1); Rd*, day respiration (CO2 evolution from nonphotorespiratory processes continuing in the light); Rubisco, ribulose-1,5-bisphosphate carboxylase/oxygenase; RUBP, ribulose-1,5-bisphosphate; Tl, leaf temperature (°C); UTPU*, rate of triose phosphate utilization; Vcmax*, maximum Rubisco carboxylase activity; Vcr, specific activity of Rubisco (μmol CO2[g Rubisco]–1 s–1] *given in either μmol m–2 s–1 or in μmol g–1 s–1 as described in the text.
Keywords: nitrogen; nutrient imbalances; phosphate limitation; phosphorus nutrition; photosynthetic electron transport; Rubisco

Responses to elevated atmospheric CO2 concentration and nitrogen supply of Quercus ilex L. seedlings from a coppice stand growing at a natural CO2 spring - Tognetti, Roberto; Johnson D., Jon (Ann. For. Sci., 1999)
Quercus ilex acorns were collected from a population of trees with a lifetime exposure to elevated atmospheric CO2 concentration (CO2), and after germination seedlings were exposed at two [CO2] (370 or 520 μmol mol-1) in combination with two soil N treatments (20 and 90 μmol mol -1 total N) in open-top chambers for 6 months. Increasing [CO2 ] stimulated photosynthesis and leaf dark respiration regardless of N treatment. The increase in photosynthesis and leaf dark respiration was associated with a moderate reduction in stomatal conductance, resulting in enhanced instantaneous transpiration efficiency in leaves of seedlings in CO2 enriched air. Elevated [CO2] increased biomass production only in the high-N treatment. Fine root/foliage mass ratio decreased with high-N treatment and increased with CO2 enrichment. There was evidence of a preferential shift of biomass to below-ground tissue at a low level of nutrient addition. Specific leaf area (SLA) and leaf area ratio (LAR) decreased significantly in leaves of seedlings grown in elevated [CO2] irrespective of N treatment. Leaf N concentration decreased significantly in elevated [CO2] irrespective of N treatment. As a result of patterns of N and carbon concentrations, C/N ratio generally increased with elevated [CO2] treatment and decreased with high nutrient supply. Afternoon starch concentrations in leaves did not increase significantly with increasing [CO2], as was the case for morning starch concentrations at low-N supply. Starch concentrations in leaves, stem and roots increased with elevated [CO2] and decreased with nutrient addition. The concentration of sugars was not significantly affected by either CO 2 or N treatments. Total foliar phenolic concentrations decreased in seedlings grown in elevated [CO 2] irrespective of N treatment, while nutrient supply had less of an effect. We conclude that available soil N will be a major controlling resource for the establishment and growth of Q. ilex in rising [CO 2] conditions
Keywords: carbon physiology; elevated [CO2]; natural CO2 springs; nitrogen; Quercus ilex

Effects of long-term elevated CO2 on foliage characteristics of Quercus ilex L. and Juniperus communis L. - Verkaik, E; Bartelink, H H (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
To study the effects of long-term elevated CO2 on Quercus ilex and Juniperus communis, leaves from plants growing close to a natural CO2 spring and from plants at a control site were collected and analyzed. Starch concentrations in leaves were found to be higher for plants growing under high CO2. Nitrogen concentrations were lower, but only in Juniperus communis. No differences in stomatal densities were found. The results indicate that in a CO2 -elevated environment, growth of both species will be different: Quercus ilex will be able to take advantage of the higher CO2 levels in spring, whereas in both species limited sink availability in the middle of the growing season will result in increased starch concentrations.
Keywords: CO2-springs; nitrogen; starch; stomatal density

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
The following values have no corresponding Zotero field: publisher: Gustav Fischer Verlag, Stuttgart
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a.; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Seasonal water potential changes and proline accumulation in Mediterranean shrubland species - Lansac, A R; ZABALLOS, J P; Martin, A (Plant Ecology, 1994)
We studied the water relations of 6 shrub and 3 tree species typical of the mediterranean climate region of central Spain to identify differential responses to water stress between and within species, and to determine if free proline concentration in leaves could be used as a water stress indicator. Predawn and midday water potentials (ffdw) on a seasonal basis, relative water content (RWC), leaf mass per area, foliar nitrogen and free proline concentrations were measured. The lowest water potentials were observed at the end of the summer, with recovery to higher water potentials in the fall and winter seasons. Species differed regarding the annual qdw fluctuation. Thymus zygis, Halimium viscosum, Genista hirsuta and Juniperus oxycedrus exhibited the most negative midday and predawn ~ w (both less than -6 MPa) with a large magnitude of response to changing conditions in soil moisture of the upper horizon of the soil. Lavandula pedunculata and Cistus ladanifer showed a moderate response. Quercus rotundifolia, Quercus faginea and Retama sphaerocarpa showed a modest response. The ~ w of different size individuals of Quercus rotundifolia and Cistus ladanifer were compared. The annual fflw fluctuation was greater in small individuals as compared to large individuals. In every species, there was an increase in proline concentration of bulk leaf tissues when predawn kVw dropped below -5 MPa. Small plants of Cistus ladanifer reached lower water potentials and also higher concentration of proline than bigger plants. Proline could possibly be used as a drought stress indicator in every species except Q. rotundifolia. It is suggested that in addition to water stress avoidance due to deep root systems, some mechanisms of water stress tolerance may operate among shrub and tree species of central Spain.
Keywords: Cistus ladanifer; Genista hirsuta; Halimium viscosum; Juniperus oxycedrus; Lavandula pedunculata; Leaf mass per area; nitrogen; Proline; Quercus faginea; Quercus rotundifolia; Relative water content; retama sphaerocarpa; Thymus zygis; water potential

Effects of leaf longevity and retranslocation efficiency on the retention time of nutrients in the leaf biomass of different woody species - Escudero, a; Arco, J. M.; Sanz, I. C.; Ayala, J. (Oecologia, 1992)
A study was made of the retention times of N and P in the leaf biomass and their relationship with the retranslocation percentages and the leaf longevities in some woody species in Central Spain. The retention times of both nutrients were strongly related to the nu- trient status of each species. These results suggest that a prolonged retention time is a way of increasing nutrient use efficiency in conditions of low nutrient availability. Plants can increase the retention time of nutrients in their leaf biomass by means of an increase in leaf longevity and/or by means of an increase in retranslocation effi- ciency. However, the effect of the retranslocation effi- ciency on retention times was almost negligible compared with the effect of leaf longevity. This suggests that an increase in leaf longevity is probably the best adaptation for increasing efficiency in the use of nutrients.
Keywords: leaf longevity; nitrogen; Nutrient use efficiency; phosphorus; retranslocation

Nitrogen immobilization in leaf litter at two Mediterranean ecosystems of SW Spain - Gallardo, Antonio; Merino, J (Biogeochemistry, 1992)
Nitrogen immobilization in relation to the dynamics of lignin and tannins in nine different types of leaf litter was investigated during a 2-yr study at two Mediterranean ecosystems of SW Spain. Net nitrogen immobilization for all the species was higher in a forest than in the more nutrient-poor soil of a shrubland. Absolute amount of lignin increased in both ecosystems in the first 2-4 months whereas tannin rapidly decreased in the same time period. Increases in lignin were significantly correlated to losses of tannins during decomposition. Initial tannin content was the best predictor of the maximum amount of immobilized nitrogen in litter in both ecosystems. Mechanisms that could explain the immobilization of nitrogen in litter are discussed.
Keywords: immobilization; leaf litter decomposition; Lignin; Mediterranean ecosystem; nitrogen; tannin

Effects of fire on soil carbon and nitrogen in a Mediterranean oak forest of Algeria - Rashid, G H (Plant and Soil, 1987)
The effects of wildfire on the dynamics of pH, organic C, total and mineral N and in vitro C and N mineralization were investigated in the soil under oak (Quercus suber L.) trees. Soil samples were taken from 5 to 21 months subsequent to the fire. The pH increased sharply in the burned surface soil (0-5 cm) taken 5 months after the fire and dropped only by half a unit over 14 to 21 months. However, at greater depth (5-15 cm), the burned soil was more acidic than the adjacent unburned soil up to 9 months following the fire, and thereafter its pH rose only slightly above that of the unburned soil. There were sharp rises in the concentration of organic C, total and mineral N in addition to in vitro mineralization activities in the burned surface soil collected 5 months after the fire; these dropped off in the subsequent samples approaching or falling below the values obtained in the unburned surface soil after 21 months. At a depth of 5-15 cm only slight or no increases over unburned soil were evident.
Keywords: Carbon; forest soil; mineralization; nitrogen; pH; Wildfire